The effect of PV modules on temperature conditions of nearby power cables - Czapp, Stanislaw; Szultka, Seweryn; Tomaszewski, Adam; Khan, Laiq (Frontiers in Energy Research, 2025)
The highest permissible load of power cables (ampacity) depends strongly on the ambient temperature, which in the case of cables surrounded by free air is generally assumed to be 25°C. Considering the installation of photovoltaic (PV) modules, the thermal conditions for the cables connected to these modules may be very unfavorable. The cables are laid under the module and the space underneath it is heated by this module. The aim of the paper is to present a numerical model of an example PV module mounted on the roof of a building, as well as the results of numerical calculations of the temperature around the module. Based on the numerical model of the PV system and advanced calculations it is possible to introduce a correction factor to determine the ampacity of the power cables located in the vicinity of the PV module. The authors’ research allows for the correct determination of the cable ampacity, avoiding its overheating and preventing the risk of fire.